Bill on high risk suppliers (Ius Novum, 2024)
The subject of the article is the introduction into the Polish legal system of cybersecurity regulations regarding infrastructure providers for the provision of 5G technology services. In particular, the implementation of the recommendations from the report prepared by the Network and Information System Cooperation Group entitled Cybersecurity of 5G networks EU Toolbox of risk mitigating measures (“5G Toolbox”). Following the recommendations of the European Commission, Poland has undertaken work to introduce regulations that would implement the provisions of the 5G Toolbox regarding high-risk suppliers. An amendment to the Act on the National Cybersecurity System of July 3, 2023 (“Draft”) has been prepared, which includes recommendations from the 5G Toolbox. The article will carry out an analysis in order to answer the question whether the provisions of the Draft regarding proceedings in the case of the so-called high-risk suppliers are consistent with the Constitution and basic procedural principles, and in particular whether legal guarantees have been provided for participants in the proceedings regarding high-risk suppliers. The research hypothesis is that not all proposed regulations in this area meet the previously indicated requirements. The analysis will take into account the proposed regulations regarding: proceedings regarding the recognition of a supplier as a high-risk supplier; application of the provisions of the Code of Administrative Procedure in these proceedings and the content of issued decisions and remedies. Mainly the dogmatic-legal method, as well as the theoretical-legal method, will be used.
Keywords: infrastructure, high risk vendors, cybersecurity, exclusion from deliveries